KONSEP DIVERSI TERHADAP ANAK PENYANDANG DISABILITAS SEBAGAI PELAKU TINDAK PIDANA DALAM SISTEM PERADILAN PIDANA ANAK - Raharjo, Trisno; Astuti, Laras (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2017)
This study aims to determine the concept of diversion in the criminal justice system of children for children with disabilities as perpetrators of criminal acts. The pattern of life in a society that is influenced by the development of information technology makes it easier for crime to reach children, as a person who is still vulnerable to committing a crime, including for certain children with disabilities. Children as perpetrators of criminal acts will go through stages in the criminal justice system of children. Diversion is one of the hallmarks of the criminal justice system. Thus, the researcher wants to know the concept of diversion in the settlement of crime committed by the child as a person with disability. This research is a doctrinal normative legal research with conceptual approach and approach of law. Normative legal research based on secondary legal material as a study material to look for principles, doctrines and sources of law in the philosophical, sociological and juridical sense. This study will analyze some cases in several District Courts in Yogyakarta Special Region. The research result’s is found some arrangement of criminal law to children with disability. The concept of diversion against children with disabilities as perpetrators of criminal offenses can not be implemented based on the results of judicial review of the verdicts on divrsion in the criminal justice system